Power Transfer Efficiency in The Inductive RF Ion Source - V. Voznyi (Журнал нано- та електронної фізики)
A radio-frequency inductive ion source without magnetic field was analyzed at driving frequency of 27,12 MHz. Diameter of the source discharge chamber is 3 cm, length is 8 cm. External electrical parameters of a source such as the coil current and the coil voltage were measured over a power range of 10÷400 W and gas (argon) pressures ranging from 0,1 to 1 Pa. The transformer model of an RF inductive discharge was applied to calculate the power transfer efficiency to plasma of the ion source. The power absorbed by plasma is determined to be 75 % in the generator power range 50÷400 W at the gas pressure of 0,5 Pa.